PESAN MORAL BALASAN AMAL PERBUATAN DALAM QS. LUQMAN AYAT 16 - Subki, Tajudin; Sri Lestari, Dian; Ni'am, Chikmatun (STAI Asy-Syukriyyah, 2024)
This article discusses the moral message about retribution for good deeds contained in Surah Luqman verse 16, seen from the perspective of Al-Jailani's interpretation. Surah Luqman is part of the Koran which contains moral instructions and valuable wisdom. Verse 16 of this surah specifically highlights the principle of just reward from Allah SWT for human actions. Tafsir Al-Jailani places emphasis on the deep meaning of this verse, highlighting that every human action will have its own consequences. The analysis in this article reveals that the moral message contained in this verse emphasizes the importance of awareness of the consequences of every action carried out by humans, both in relation to others and to the Creator. By understanding this principle, people are expected to be able to develop a responsible attitude in everyday life and pay more attention to the consequences of every action they take.